2015
DOI: 10.1111/ane.12414
|View full text |Cite
|
Sign up to set email alerts
|

Lacosamide cardiac safety: clinical trials in patients with partial-onset seizures

Abstract: Evaluation of the pooled cardiac safety data from patients with POS showed that adjunctive lacosamide at the maximum recommended dose (400 mg/day) was not clearly associated with any cardiac effect other than a small, dose-related increase in PR interval that had no evident symptomatic consequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 28 publications
(30 reference statements)
2
20
0
1
Order By: Relevance
“…The safety of lacosamide is further supported by a comprehensive analysis of the cardiac safety data pooled from 1304 patients who took part in the registration trials for lacosamide in the treatment of POS. This analysis showed no specific cardiac risks, aside from the small, dose-related increase in PR interval, with no evident symptomatic consequence [19]. Furthermore, a positively controlled QTc trial in healthy volunteers showed no detrimental effect associated with lacosamide use at approved dosages [20].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The safety of lacosamide is further supported by a comprehensive analysis of the cardiac safety data pooled from 1304 patients who took part in the registration trials for lacosamide in the treatment of POS. This analysis showed no specific cardiac risks, aside from the small, dose-related increase in PR interval, with no evident symptomatic consequence [19]. Furthermore, a positively controlled QTc trial in healthy volunteers showed no detrimental effect associated with lacosamide use at approved dosages [20].…”
Section: Discussionmentioning
confidence: 75%
“…Cardiac conduction side effects are associated with the use of several AEDs, particularly those that block sodium channels [14][15][16][17]. A small dose-related increase in the PR interval has been observed in trials of oral and intravenous lacosamide, with no significant change in blood pressure or QTc interval [11][12][13][18][19][20]. There have also been some published reports of cardiac AEs in patients receiving lacosamide [9,18,[21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…A total of three cardiac TEAEs were reported during lacosamide treatment in patients with CVEE. Analyses of pooled cardiac safety data from three randomized, placebo‐controlled trials of adjunctive lacosamide in patients with focal seizures showed no clear cardiac effects at the maximum recommended dose (400 mg/day) other than a small dose‐related increase in PR interval . Lacosamide should be used with caution in patients with underlying proarrhythmic conditions (known cardiac conduction problems, severe cardiac disease, and cardiac sodium channelopathies), as well as in patients taking concomitant medications that affect cardiac conduction or prolong the PR interval…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac safety issues were analyzed in a pooled analysis that showed a dose‐dependent prolongation of PR interval from baseline to the end‐of‐maintenance from 1.4 msec (LCM 200 mg/day), 4.4 msec (LCM 400 mg/day), to 6.6 msec (LCM 600 mg/day). The frequency of first‐degree AV block differed between 1.1% and 4.9% on LCM compared to placebo with 2.4–3.2%.…”
Section: Special Considerations In Populations With Renal Hepatic Omentioning
confidence: 99%